Особенности монетарного механизма развития экономики Китая - Вишневский, В.П.; Матюшин, А.В.; Вишневская, Е.Н. (Економіка промисловості, 2015)
Проанализированы современные особенности монетарного механизма Китая и ожидаемые эффекты его функционирования с учётом новых экономических, институциональных и геополитических обстоятельств развития, обусловленных, в частности, мировым финансовым кризисом 2007-2008 гг. и экономическим подъёмом мирового Юга. Определены возможности адаптации китайского опыта для решения новых задач, которые стоят перед экономикой Украины в целом и её промышленностью в частности на современном этапе развития. Проаналізовано сучасні особливості монетарного механізму Китаю та очікувані ефекти його функціонування з урахуванням нових економічних, інституціональних та геополітичних обставин розвитку, обумовлених, зокрема, світовою фінансовою кризою 2007-2008 рр. та економічним підйомом світового Півдня. Визначено можливості адаптації китайського досвіду для вирішення нових завдань, які стоять перед економікою України в цілому та її промисловістю зокре-ма на сучасному етапі розвитку. The article deals with the modern features of monetary mechanism of China and expected effects of its operation taking into account new economic, institutional and geopolitical circumstances of its development caused, in particular, by the global financial crisis of 2007-2008 and the economic recovery of the global South. The possibility of adapting the Chinese experience to meet the new challenges facing the economy of Ukraine in general and its industry, in particular, at the present stage of development is determined. It is concluded that now, when the Chinese economy has become the first in the world (taking into account PPP) and it is moving to a new stage of its development, the monetary mechanism of economic growth is changing to the "market" direction, but gradually and consistently. Monetary authorities neither recklessly perform the insistent recommendations of international financial institutions to accelerate the creation of a more liberal financial system nor exclude them, but they adapt well-known Western monetary instruments to the specific problems of national development after they are tested in practice. China's success of really planetary scale and consequences have been achieved with the direct participation of the central bank, which provides oversight and control over the financial sector under the leadership of the State Council of China with the dominance of large state-owned banks in the structure the financial system, "non-market" consistently low rate of CNY in relation to the US dollar and "non-market" interest rates on deposits and loans, and an undeveloped stock market. Within the next years China's economy will gradually slow down in line with the strategy of the government to ensure a balanced economic growth. It will be maintained by low oil prices and the prospects for global economic growth that are slightly better than it was expected before, and the possibility of a sharp correction in the property market and increasing indebtedness of local authorities remain among the major risks. Monetary policy is crucial in transition to such a model, and in conjunction with other regulatory tools of mixed economy it is aimed at achieving macroeconomic and financial stability, efficient allocation of scarce resources, and mitigation of shocks of internal and external origin.